(3GdJOhjd HGdLGeYGJ GdeUQjI aj VhA NHQGJ HYV GdOhd (B:s (3JUhQ ebJQM (B/s - (3,eQje eMehO CMeO eSdhHs; (3OYGA YKeGf YRej s; (3eMeO GdSjO aQL CdeGXs (2024)
(3gOaJ GdOQGSI GdMGdjI Edi JYQa GdEWGQ GdeaGgjej ddJOhjd HGdLGeYGJ, hJYQa CHQR GdNHQGJ GdOhdjI aj eLGd GdJOhjd HGdLGeYGJ, hJYQa LghO GdJOhjd HGdLGeYGJ GdeUQjI Ydi GdeSJhi GdhWfj hGdeDSSj, hcTa hGbY GdJOhjd HLGeYI GdbGgQI HGdfSHI deYhbGJg heJWdHGJg, hGYJeOJ GdOQGSI Ydi GdefgL GdhUaj, hGSJNOeJ GdGSJHGfI COGI dLeY GdHjGfGJ, hbO Je JhRjYgG Ydi CYVGA gjFI GdJOQjS HLGeYI GdbGgQI, hCXgQJ GdfJGFL MJejI GdJZdH Ydi eYhbGJ GdJOhjd HGdLGeYGJ GdeUQjI, hVQhQI JhajQ eJWdHGJ GdJOhjd HGdLGeYGJ GdeUQjI, dfLGM JfajPg, haj GdNJGe bOeJ GdOQGSI JUhQ ebJQM ddJOhjd HGdLGeYGJ GdeUQjI, GfWdGbG ef GSJYQGV GdfJGFL GdeJUdI HGdLGfH GdfXQj hGdejOGfj ddOQGSI, hJeKd Pdc aj gOa hadSaI hefWdbGJ hBdjGJ JfajP GdJUhQGdebJQM(B.s
The current study aimed to identify the conceptual framework of internationalization at universities, identify the most prominent international experiences in the field of internationalization at universities, identify internationalization efforts in Egyptian universities at the national and institutional levels, and reveal the reality of internationalization at Cairo University in terms of its obstacles and requirements. The study relied on the descriptive approach, and used the questionnaire as a tool for collecting data, which was distributed to faculty members at Cairo University. The results showed the inevitability of overcoming the obstacles to internationalization at Egyptian universities, and the necessity of providing internationalization requirements at Egyptian universities for its successful implementation. In conclusion, the study presented a suggested conception for internationalization at Egyptian universities, based on a review of the results related to the theoretical and field aspects of the study, and this was represented in the goal, philosophy, starting points and mechanisms for implementing the suggested conception.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B256-280.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdJYdje GdYGdjs -- (3eUQs; (3GdJOhjd HGdLGeYGJs -- (3JOhjd GdJYdje GdYGdjs -- (3GdLGeYGJ GdeUQjIs